Zespół MELAS czy Leigh, jak zróżnicować? - Finsterer, Josef (Pediatric Endocrinology Diabetes and Metabolism, 2021)
With interest we read the article by Baszyńska-Wilk et al. about a 12 years old female who was diagnosed with mitochondrial encephalopathy, lactic acidosis, and stroke-like episodes (MELAS) syndrome upon the clinical presentation, blood tests, and the cerebral magnetic resonance imaging (MRI) [1]. The diagnosis was neither confirmed by biochemical nor by genetic investigations [1]. The study is appealing but raises the following concerns.